Our Experience Managing Difficult Accidental Chainsaw Trauma. Issue 7 (October 2019) - Cascino, Flavia; Pini, Niccolò; Giovannoni, Maria Elisa; Aboh, Ikenna Valentine; Gabriele, Guido; Niccolai, Gianluca; Zerini, Federico; Amadi, Jude Ugochukwu; Gennaro, Paolo
Abstract : Background: Chainsaw and circular-saw injuries represent a rare condition within the maxillofacial region. The purpose of this clinical report is to describe the injuries and the clinical and surgical management of these rare traumas. Methods: In this clinical report, 11 patients presenting themselves to the emergency room in the hospital "Policlinico Le Scotte, " Siena, from March 2016 to September 2017 with severe chainsaw and circular-saw injuries, were included. All of the patients underwent general anesthesia and surgical treatment. This study describes 3 of the 11 patients with saw injuries. Results: No complications occurred during surgeries and a good primary closure of the wound margins were achieved in all patients. However, after surgery, the authors experienced some complications in 2 patients: the 1st one displayed chewing problems due to extensive local edema; the 2nd one developed a total loss of vision in his left eye, even though there was no damage inflected to the eye ball during the trauma or surgery. Conclusion: All the patients were followed during the 1st year after surgery. The authors evaluated the patients at 3 months, 6 months, and after 1 year, and none of them developed complications or alterations related to the trauma. However, 1 patient is still experiencing loss of vision and he is under constant specialized follow-up. Abstract : Supplemental Digital Content is available in the text